Open Access Influence on Argentinean Scientific Community's Publishing Patterns - Miguel, Sandra; Gómez, Nancy Diana; Bongiovani, Paola
Este estudio tiene como objetivo estimar la influencia del acceso abierto en los patrones de publicación de la comunidad científica argentina en diferentes campos temáticos (Medicina; Física y Astronomía; Agricultura y Ciencias biológicas y Ciencias sociales y Humanidades), a partir del análisis del modelo de acceso de las revistas elegidas para comunicar los resultados de investigación en el período 2008-2010. La producción fue recogida de la base de datos SCOPUS y los modelos de acceso de las revistas determinados a partir de la consulta a las fuentes DOAJ, e-revist@s, SCielo, Redalyc, PubMed, Romeo-Sherpa y Dulcinea. Se analizó la accesibilidad real y potencial de la producción científica nacional por las vías dorada y verde, respectivamente, así como también por suscripción a través de la Biblioteca Electrónica de Ciencia y Tecnología del Ministerio de Ciencia, Tecnología e Innovación Productiva de la Nación Argentina. Los resultados muestran que en promedio, y para el conjunto de las temáticas estudiadas, el 70de la producción científica argentina visible en SCOPUS se publica en revistas que adhieren de una u otra forma al movimiento de acceso abierto, en una relación del 27para la vía dorada y del 43para las que permiten el autoarchivo por la vía verde. Entre el 16y el 30(según las áreas temáticas) de los artículos publicados en revistas que permiten el autoarchivo se accede vía suscripción. El porcentaje de revistas sin acceso es del orden del 30en Ciencias Sociales y Humanidades, y alcanza cerca del 45en el resto de las áreas. Se concluye que Argentina presenta condiciones muy favorables para liberar un alto porcentaje de la literatura científica generada en el país bajo la modalidad del acceso abierto a través de repositorios institucionales y de mandatos para el auto-archivo, contribuyendo además a incrementar la accesibilidad y la preservación a largo plazo de la producción científica y tecnológica nacional
The objective of this study is to estimate the influence of Open Access on publication patterns of the Argentina scientific community in different disciplines (Medicine; Physics and Astronomy; Agriculture and Biological Sciences; and Social Sciences and Humanities), based on an analysis of the access model that the chosen journals used to communicate their research results during 2008-2010. The sample was taken from the SCOPUS database and the open access models were selected through searches done using the following sources: DOAJ, e-revist@s, SCielo, Redalyc, PubMed, Romeo--?Sherpa, and Dulcinea. The real and potential accessibility of national scientific production was analyzed following both golden and green routes, respectively, as well as through subscription to the Science and Technology Electronic Library that belongs to the Argentinean Ministry of Science, Technology and Productive Innovation. Our results show that, on average, and involving the studied group of themes as a whole, 70of internationally visible Argentinean scientific production is published in journals that, in one way or another, adhere to the Open Access movement, with a ratio of 27for the golden route and 43for the green route, with variations according to areas of academic discipline. Between 16and 30(according to areas) of the articles that were published in journals that adhere to the green route were accessed via subscription. The percentage of journals without access is around 30for Social sciences and Humanities, and it reaches nearly 45for the other areas. In conclusion, Argentina offers very favorable conditions to release a high percentage of the scientific literature that is generated in the country through Open Access options, as well as to optimize its investment in journal subscriptions through an increase in the number of publications that are available via institutional repositories and self-archiving mandates, contributing also to increased visibility and long-term preservation for its national scientific and technological production
Authors thanks the Argentinean Minister of Education for funding the project (Ref. H540)